Defenses against Virus and Vector: A Phloem-Biological Perspective on RTM- and SLI1-Mediated Resistance to Potyviruses and Aphids - Kloth, Karen J.; Kormelink, Richard (Viruses, 2020)
Combining plant resistance against virus and vector presents an attractive approach to reduce virus transmission and virus proliferation in crops. Restricted Tobacco-etch virus Movement (RTM) genes confer resistance to potyviruses by limiting their long-distance transport. Recently, a close homologue of one of the RTM genes, SLI1, has been discovered but this gene instead confers resistance to Myzus persicae aphids, a vector of potyviruses. The functional connection between resistance to potyviruses and aphids, raises the question whether plants have a basic defense system in the phloem against biotic intruders. This paper provides an overview on restricted potyvirus phloem transport and restricted aphid phloem feeding and their possible interplay, followed by a discussion on various ways in which viruses and aphids gain access to the phloem sap. From a phloem-biological perspective, hypotheses are proposed on the underlying mechanisms of RTM- and SLI1-mediated resistance, and their possible efficacy to defend against systemic viruses and phloem-feeding vectors.